Analytic Hierarchy Process untuk Pendukung Keputusan Prioritas Perbaikan Standar Akreditasi Sekolah - Vika Febri Muliati; Eki Saputra (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
School accreditation activity is an activity undertaken to assess the quality level of each school. Implementation of accreditation under the auspices of the National Accreditation Board of School / Madrasah (BAN-S / M). At the district level task BAN-S / M aided by the Accreditation Implementation Unit (UPA). Accreditation assessment based on the National Education Standards (NES) which consists of content standards, standards of process, competency standards, standards of teachers and education personnel, standards of facilities and infrastructure, management standards, standards of financing, and standards of educational assessment In Indragiri Hilir in years 2007-2015 UPA has accredited 160 SMP. From the results of the accreditation of the period data showed that 54% of SMP in Indragiri Hilir has lower accreditation. One reason is the school not knowing how to repair priority decision determination standards of accreditation.Decision Support System (DSS) is needed to ableto determine prioritize improvements accreditation standards. AHP is a method to solve a complex problem into a hierarchy and generate the highest priority. Prioritization of repairs done on the accreditation criteria of sufficiency of funds, availability of resources, a period of improvement and weight rating BAN-S / M. DSS can help the school to do a repair priority setting standards for school accreditation. Keywords: Accrediation, Analytic Hierarchy Process, Decision Support System, Junior High School, priorities